Identification of the Functional Domains of the Telomere Protein Rap1 in Schizosaccharomyces pombe - Fujita, Ikumi (Public Library of Science, 2012)

(untitled)
The telomere at the end of a linear chromosome plays crucial roles in genome stability. In the fission yeast Schizosaccharomyces pombe, the Rap1 protein, one of the central players at the telomeres, associates with multiple proteins to regulate various telomere functions, such as the maintenance of telomere DNA length, telomere end protection, maintenance of telomere heterochromatin, and telomere clustering in meiosis. The molecular bases of the interactions between Rap1 and its partners, however, remain largely unknown. Here, we describe the identification of the interaction domains of Rap1 with its partners. The Bqt1/Bqt2 complex, which is required for normal meiotic progression, Poz1, which is required for telomere length control, and Taz1, which is required for the recruitment of Rap1 to telomeres, bind to distinct domains in the C-terminal half of Rap1. Intriguingly, analyses of a series of deletion mutants for rap1 (+) have revealed that the long N-terminal region (1–456 a.a. [amino acids]) of Rap1 (full length: 693 a.a.) is not required for telomere DNA length control, telomere end protection, and telomere gene silencing, whereas the C-terminal region (457–693 a.a.) containing Poz1- and Taz1-binding domains plays important roles in those functions. Furthermore, the Bqt1/Bqt2- and Taz1-binding domains are essential for normal spore formation after meiosis. Our results suggest that the C-terminal half of Rap1 is critical for the primary telomere functions, whereas the N-terminal region containing the BRCT (BRCA1 C-terminus) and Myb domains, which are evolutionally conserved among the Rap1 family proteins, does not play a major role at the telomeres.